Cerebral perivascular spaces as an important diagnostic marker of cerebral small vessel disease and brain pathology - S. P. Moskovko; S. R. Bartiuk (Kazimierz Wielki University, 2020)
Objective. To assess the association of enlarged perivascular spaces (EPVS) with cerebral small vessel disease (CSVD), some basic metabolic tests, brain atrophy and clinical outcome after territorial stroke. Methods. 90 patients with acute stroke (<24 hours of onset) were recruited. Modified Rankin scale and Bartel index where used to assess stroke outcome. Cerebral MRI was performed to assess white matter lesions (WML), lacunes, cerebral atrophy and EPVS in basal ganglia and cortical-subcortical area with a validated four-point visual rating scale. Total CSVD burden was calculated with summation of lacunes, WML and EPVS with a validated scale. Spearmen correlation and logistic regression were used to identified association between EPVS, total CSVD burden, CSVD features and some basic metabolic tests (creatinine, urea, cholesterol, bilirubin, fibrinogen, erythrocyte sedimentation rate). Results. There was a very strong correlation between EPVS and total CSVD burden (r = 0.9, p <0.000) and with Fazekas score scale (r = 0.9, p <0.000). A strong correlation was found between EPVS and global cortical atrophy (r = 0.7, p <0.000), and a moderate correlation with presence of lacunes (r = 0.4, p <0.05). EPVS in basal ganglia had a significant correlation with the degree of extracranial carotid stenosis (r = 0.4, p <0.05). The severity of EPVS was associated with a more severe neurological deficit on the NIHSS scale (r = 0.5, p <0.05) and an increased degree of disability by Bartel's index (r = 0.5, p <0.05) in patients on discharge. Creatinine was associated with CSVD features. Conclusions. EPVS is highly associated with total CSVD burden and others its features as well as with stroke outcome. EPVS in different brain regions may lead to the distinguish of two main type of CSVD - hypertensive arteriolosclerosis and beta-amyloid angiopathy.